Thermoplastic resin composition

By developing a thermoplastic resin composition containing specific monomers and polymers, the shortcomings of existing medical transparent materials in multiple properties are solved, and excellent comprehensive performance and the effect of reducing manufacturing costs are achieved.

CN114402026BActive Publication Date: 2025-02-18LG CHEM LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202180005368.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-03-30
Filing Date
2021-03-31
Publication Date
2025-02-18
Estimated Expiration
2041-03-31

AI Technical Summary

Technical Problem

Existing medical transparent materials have shortcomings in terms of transparency, impact resistance, processing properties, chemical resistance and gamma radiation resistance, and it is difficult to meet the production needs of complex products.

Method used

Developed a thermoplastic resin composition, including a rubber polymer, a first styrene monomer unit, a diene monomer unit, a (meth)acrylate monomer unit and a second styrene monomer unit, by Adjust composition and average particle size to optimize its performance.

Benefits of technology

Excellent performance in transparency, impact resistance, processing properties, chemical resistance and gamma radiation resistance are achieved, and the amount of (meth)acrylate monomer is used is reduced, thereby reducing the manufacturing cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003549247660000201
    Figure BDA0003549247660000201
  • Figure BDA0003549247660000211
    Figure BDA0003549247660000211
  • Figure BDA0003549247660000221
    Figure BDA0003549247660000221
Patent Text Reader

Abstract

The present invention provides a thermoplastic resin composition, comprising: a rubber polymer, the rubber polymer comprising a first styrene monomer unit and a diene monomer unit in a weight ratio of 10:90 to 35:65, and an average particle size of 250 to 450 nm; a (meth)acrylate monomer unit; and a second styrene monomer unit, wherein the weight ratio of the (meth)acrylate monomer unit to the second styrene monomer unit is 2 or less, and the weight average molecular weight is in the range of 130,000 to 250,000 g / mol.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to Korean Patent Application No. 10-2020-0060730 filed on May 21, 2020 and Korean Patent Application No. 10-2021-0041215 filed on March 30, 2021, the disclosures of which are incorporated herein by reference in their entirety. Technical Field

[0004] The present invention relates to a thermoplastic resin composition, and in particular, to a thermoplastic resin composition excellent in transparency, impact resistance, processability, chemical resistance and gamma radiation resistance. Background Art

[0005] Recently, in addition to environmental issues, many changes have taken place in the material industry. In particular, due to issues such as environmental hormones or the treatment of materials used as medical or food containers, many efforts have been made to replace conventionally used polyvinyl chloride, polycarbonate, etc. In particular, new materials need to be developed in the field of medical transparent materials for syringes and tube fittings (which are used when liquids are stored therein).

[0006] Meanwhile, polycarbonate, polymethyl methacrylate, polystyrene, polyacrylonitrile-styrene, etc. are generally used as transparent resins. Polycarbonate has excellent impact strength and excellent transparency, but its processing performance is not good, which makes it difficult to produce complex products, and its chemical resistance is not excellent. In addition, due to the use of bisphenol A in the preparation of polycarbonate, the use of polycarbonate is increasingly restricted. In addition, polymethyl methacrylate has excellent optical properties, but its impact resistance and chemical resistance are not excellent. In addition, polystyrene and polyacrylonitrile-styrene are not excellent in impact resistance and chemical resistance. In addition, diene grafted polymers have excellent impact resistance and excellent processing performance, while achieving a balance between the two, but their transparency is not excellent.

[0007] Therefore, it is necessary to develop a medical material that is excellent in transparency, impact resistance, chemical resistance, and processability. Summary of the invention

[0008] [Technical issues]

[0009] The present invention aims to provide a thermoplastic resin composition, which achieves a balance between transparency, impact resistance and processability, and can reduce the amount of (meth)acrylate monomers to improve chemical resistance and gamma radiation resistance, and reduce manufacturing costs. The present invention also aims to provide a thermoplastic resin composition that can be used for medical purposes.

[0010] [Technical solution]

[0011] One aspect of the present invention provides a thermoplastic resin composition, comprising: a rubber polymer, the rubber polymer comprising a first styrene monomer unit and a diene monomer unit in a weight ratio of 10:90 to 35:65, and an average particle size of 250 to 450 nm; a (meth)acrylate monomer unit; and a second styrene monomer unit, wherein the weight ratio of the (meth)acrylate monomer unit to the second styrene monomer unit is 2 or less, and the weight average molecular weight is in the range of 130,000 to 250,000 g / mol.

[0012] [Beneficial Effects]

[0013] The thermoplastic resin composition of the present invention is not only excellent in transparency, impact resistance, processability, chemical resistance and gamma radiation resistance, but also can reduce the amount of (meth) acrylate monomers, thereby reducing manufacturing costs. In addition, the thermoplastic resin composition can be used as a medical material. DETAILED DESCRIPTION

[0014] Hereinafter, the present invention will be described in more detail to facilitate understanding of the present invention.

[0015] The terms or words used in the present specification and claims should not be interpreted as limited to the meanings in conventional usage or in dictionaries, and the terms or words should be interpreted as meanings and concepts that are consistent with the technical spirit of the present invention, based on the principle that the inventor can appropriately define the concepts of the terms to explain the invention in the best manner.

[0016] In the present invention, the average particle size can be measured using a dynamic light scattering method, specifically, using a Nicomp 380 instrument (manufactured by Particle Sizing Systems). In the present invention, the average particle size may refer to the arithmetic mean particle size in the particle size distribution measured using a dynamic light scattering method, i.e., the average particle size based on the scattering intensity distribution.

[0017] In the present invention, the average particle size can be measured using a transmission electron microscope (TEM).

[0018] In the present invention, the refractive index refers to the absolute refractive index of the material, which is considered to be the ratio of the speed of electromagnetic radiation in free space to the speed of radiation in the material, wherein the radiation can be visible light with a wavelength of 450nm to 680nm, specifically, visible light with a wavelength of 589.3nm. The refractive index can be measured by a known method, i.e., using an Abbe refractometer.

[0019] In the present invention, after the graft copolymer and the non-graft copolymer are cut to a thickness of 0.2 mm, the refractive index may be measured using an Abbe refractometer at 25° C. under visible light of 589.3 nm wavelength.

[0020] In the present invention, the weight of the rubber polymer, the diene monomer unit, the (meth)acrylate monomer unit, the first styrene monomer unit, and the second styrene monomer unit contained in the thermoplastic resin composition can be measured by infrared (IR) spectroscopy. In this case, as an infrared spectrometer, a Nicolet TM iS20 FTIR spectrometer (manufactured by Thermo Scientific).

[0021] In the present invention, the impact modifying portion of the thermoplastic resin composition may refer to a portion consisting of a rubber polymer and a monomer unit grafted onto the rubber polymer, and the matrix portion of the thermoplastic resin composition may refer to a portion excluding the impact modifying portion and including monomer units in the graft copolymer that are not grafted onto the rubber polymer and monomer units contained in the non-graft copolymer.

[0022] In the present invention, the weight average molecular weight of the thermoplastic resin composition or the graft copolymer can be measured as a relative value relative to a standard polystyrene (PS) sample by gel permeation chromatography (GPC) after the thermoplastic resin composition or the graft copolymer is dissolved in acetone and then centrifuged to separate a supernatant and a precipitate, and the supernatant is dried, dissolved in tetrahydrofuran and filtered.

[0023] Specifically, 1 g of the thermoplastic resin composition or graft copolymer powder was dissolved in 50 g of acetone while stirring for 24 hours, and then centrifuged in a centrifuge (SUPRA30K manufactured by Hanil Science Industrial) at 16,000 rpm and -10°C for 4 hours to separate the supernatant and the precipitate, and the supernatant was dried in a hot air dryer set at 50°C for 12 hours to obtain a dry solid. The obtained dry solid was dissolved in tetrahydrofuran at a concentration of 1% by weight, and then filtered through a 1 μm filter, and then the weight average molecular weight was measured by GPC as a relative value relative to a standard PS sample.

[0024] Meanwhile, in the GPC measurement, an Agilent 1200 series system may be used, and the measurement conditions may be as follows.

[0025] Refractive index detector (RI): Agilent G1362 RID

[0026] RI temperature: 35℃

[0027] Data processing: Agilent ChemStation S / W

[0028] Solvent: Tetrahydrofuran

[0029] Column temperature: 40°C

[0030] Flow rate: 0.3ml / min

[0031] Sample concentration: 2.0mg / ml

[0032] Injection volume: 10μm

[0033] Column model: 1×PLgel 10μm MiniMix-B (250×4.6mm) + 1×PLgel 10μm MiniMix-B (250×4.6mm) + 1×PLgel 10μm MiniMix-B Guard (50×4.6mm)

[0034] Standard sample: polystyrene

[0035] In the present invention, the weight average molecular weight of the non-grafted copolymer can be measured by GPC using tetrahydrofuran as an eluent as a relative value with respect to a standard PS sample.

[0036] In the present invention, the first styrene-based monomer unit may refer to a styrene-based monomer unit included in the rubber polymer, and the second styrene-based monomer unit may refer to a styrene-based monomer unit included in the thermoplastic resin composition but not included in the rubber polymer.

[0037] In the present invention, the first styrene monomer unit and the second styrene monomer unit may each be a unit derived from a styrene monomer. The styrene monomer may be one or more selected from styrene, α-methylstyrene, α-ethylstyrene and p-methylstyrene, preferably styrene.

[0038] In the present invention, the (meth)acrylic acid ester monomer unit may be a unit derived from a (meth)acrylic acid ester monomer. The (meth)acrylic acid ester monomer may be C1 to C 10 Alkyl (meth) acrylate monomers, the C1 to C 10 The alkyl (meth)acrylate monomer can be one or more selected from methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, heptyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate and decyl (meth)acrylate, preferably methyl methacrylate.

[0039] In the present invention, the acrylonitrile monomer unit may be a unit derived from an acrylonitrile monomer. The acrylonitrile monomer may be one or more selected from acrylonitrile, methacrylonitrile, phenylacrylonitrile and α-chloroacrylonitrile, preferably acrylonitrile.

[0040] In the present invention, the diene monomer unit may be a unit derived from a diene monomer, and the diene monomer may be one or more selected from 1,3-butadiene, isoprene, chloroprene and piperylene, preferably 1,3-butadiene.

[0041] Thermoplastic resin composition

[0042] The thermoplastic resin composition according to an embodiment of the present invention includes: a rubber polymer including a first styrene monomer unit and a diene monomer unit in a weight ratio of 10:90 to 35:65, and an average particle size of 250 to 450 nm; a (meth)acrylate monomer unit; and a second styrene monomer unit, wherein the weight ratio of the (meth)acrylate monomer unit to the second styrene monomer unit is 2 or less, and the weight average molecular weight is in the range of 130,000 to 250,000 g / mol.

[0043] The inventors of the present invention have discovered that by adjusting the composition and average particle size of the rubber polymer, the weight ratio and weight average molecular weight of the second styrene monomer unit to the (meth)acrylate monomer unit contained in the thermoplastic resin composition, a thermoplastic resin composition excellent in transparency, impact resistance, processability, chemical resistance, and gamma radiation resistance is prepared, and the inventors have completed the present invention based on the above discovery.

[0044] Hereinafter, the present invention will be described in detail.

[0045] When the rubber polymer only includes diene monomer units, in order to eliminate and minimize the refractive index difference between the impact modified part and the base part of the thermoplastic resin composition, the excess (meth) acrylate monomer units must be included in the base part. However, the (meth) acrylate monomer units cause the chemical resistance of the thermoplastic resin composition to decrease, and the manufacturing cost is increased due to the high cost of the monomer. In addition, the rubber polymer can not be prepared using only styrene monomers. However, the rubber polymer according to the present invention not only includes diene monomer units, but also includes the first styrene monomer units to improve the refractive index of the rubber polymer, so that a small amount of (meth) acrylate monomer units can be included in the base part. Therefore, the thermoplastic resin composition according to the present invention can minimize the problems such as the reduction of chemical resistance and the increase of manufacturing cost caused by the (meth) acrylate monomer units.

[0046] According to an embodiment of the present invention, the rubber polymer comprises a first styrene monomer unit and a diene monomer unit in a weight ratio of 10:90 to 35:65, and preferably in a weight ratio of 15:85 to 30:70. When the above conditions are met, impact resistance can be improved and refractive index can be increased, so that the amount of (meth) acrylate monomer units can be reduced, and the reduction in chemical resistance and the increase in manufacturing cost caused by the (meth) acrylate monomer units can be minimized. However, when the content of the first styrene monomer unit is lower than the above range, chemical resistance and gamma radiation resistance may be greatly reduced. On the other hand, when the content of the first styrene monomer unit is higher than the above range, transparency and impact resistance may be greatly reduced.

[0047] Since the rubber polymer includes the diene monomer unit and the first styrene monomer unit in the above weight ratio, its refractive index is higher than that of the rubber polymer composed only of the diene monomer. Specifically, the refractive index of the rubber polymer may be 1.5230 to 1.5420, preferably 1.5300 to 1.5400.

[0048] In addition, the average particle size of the rubber polymer contained in the thermoplastic resin composition according to the embodiment of the present invention can be 250 to 450 nm, preferably 300 to 350 nm. When the thermoplastic resin composition according to the embodiment of the present invention includes a rubber polymer having an average particle size lower than the above range, the processing performance and impact resistance may be greatly reduced. On the other hand, when the thermoplastic resin composition includes a rubber polymer having an average particle size higher than the above range, the surface gloss property may be reduced, and it is not preferred to prepare the rubber polymer by emulsion polymerization because the latex stability of the rubber polymer is greatly reduced.

[0049] In the thermoplastic resin composition according to the embodiment of the present invention, the weight ratio of the (meth) acrylate monomer unit to the second styrene monomer unit can be less than 2, preferably 0.8 to 2. The weight ratio of the (meth) acrylate monomer unit to the second styrene monomer unit exceeds 2, which means that an excessive amount of (meth) acrylate monomer units is included, and when the weight ratio of the (meth) acrylate monomer unit to the second styrene monomer unit exceeds 2, the chemical resistance of the thermoplastic resin composition will be significantly reduced, and the manufacturing cost will be increased due to the addition of excessive (meth) acrylate monomers. On the other hand, when the weight ratio of the (meth) acrylate monomer unit to the second styrene monomer unit is less than 0.8, impact resistance may be reduced.

[0050] The thermoplastic resin composition according to an embodiment of the present invention may have a weight average molecular weight of 130,000 to 250,000 g / mol, preferably a weight average molecular weight of 140,000 to 210,000 g / mol. The weight average molecular weight refers to the weight average molecular weight of a thermoplastic resin composition (i.e., a thermoplastic resin composition comprising an impact-modified portion and a matrix portion) comprising a graft copolymer and a non-graft copolymer to be described below. When the weight average molecular weight of the thermoplastic resin composition is lower than the above range, the chemical resistance of the thermoplastic resin composition may be reduced, and when higher than the above range, the processing properties of the thermoplastic resin composition may be reduced.

[0051] Meanwhile, the thermoplastic resin composition according to an embodiment of the present invention may include: 20.00 wt % to 40.00 wt % of a rubber polymer; 23.00 wt % to 51.00 wt % of a (meth) acrylic acid ester monomer unit; and 18.00 wt % to 41.00 wt % of a second styrene monomer unit. Preferably, the thermoplastic resin composition includes: 27.00 wt % to 37.00 wt % of a rubber polymer; 27.00 wt % to 45.00 wt % of a (meth) acrylic acid ester monomer unit; and 22.00 wt % to 37.00 wt % of a second styrene monomer unit. When the above conditions are met, a thermoplastic resin composition having improved performance in terms of impact resistance, chemical resistance and processing performance can be prepared.

[0052] The thermoplastic resin composition according to an embodiment of the present invention may further include an acrylonitrile monomer unit to further improve chemical resistance. The acrylonitrile monomer unit may be included in an amount of 3.00 wt % to 12.00 wt %, preferably 5.00 wt % to 10.00 wt %, to improve chemical resistance and minimize the occurrence of yellowing.

[0053] Meanwhile, the thermoplastic resin composition according to an embodiment of the present invention may include a graft copolymer and a non-graft copolymer.

[0054] The refractive index of the graft copolymer may be 1.5230 to 1.5420, preferably 1.5300 to 1.5400. When the above range is met, the refractive index of the graft copolymer is the same as or similar to that of the rubber polymer, so the transparency of the graft copolymer can be further improved.

[0055] The refractive index of the graft copolymer may differ from the refractive index of the non-graft copolymer by 0.0100 or less, and preferably the difference is 0. When the above conditions are met, the thermoplastic resin composition may become more transparent.

[0056] The weight ratio of the graft copolymer to the non-graft copolymer may be 40:60 to 80:20, preferably 50:50 to 70:30. When the above range is met, the processing performance can be further improved without reducing the impact resistance.

[0057] The graft copolymer may include a rubber polymer including a first styrene-based monomer unit and a diene-based monomer unit and having an average particle size of 250 to 450 nm, a (meth)acrylate-based monomer unit grafted onto the rubber polymer, and a second styrene-based monomer unit grafted onto the rubber polymer.

[0058] The rubber polymer included in the thermoplastic resin composition according to an embodiment of the present invention may be the same as the rubber polymer included in the graft copolymer.

[0059] The graft copolymer may include a (meth)acrylate-based monomer unit and a second styrene-based monomer unit which are not grafted onto the rubber polymer.

[0060] At the same time, the transparency of the graft copolymer can be determined by the refractive index of the rubber polymer and the shell including the monomer unit grafted onto the rubber polymer. Moreover, the refractive index of the shell can be adjusted by the mixing ratio of the monomer unit. That is, the refractive index of the rubber polymer and the shell needs to be similar to each other, and preferably their refractive indexes are the same. Therefore, the refractive index of the rubber polymer included in the graft copolymer can differ from the refractive index of the monomer unit grafted onto the rubber polymer by less than 0.0100, and the preferred difference is 0. When the above conditions are met, the thermoplastic resin composition can become more transparent.

[0061] The graft copolymer may contain 30.00 wt % to 65.00 wt % of the rubber polymer, preferably 35.00 wt % to 60.00 wt % of the rubber polymer. When the above range is met, excellent impact resistance can be exhibited, and grafting is fully carried out in the preparation of the graft copolymer, so the graft copolymer can achieve excellent transparency.

[0062] The rubber polymer may include a first styrene monomer unit and a diene monomer unit in a weight ratio of 10:90 to 35:65, preferably in a weight ratio of 15:85 to 30:70. When the above conditions are met, impact resistance can be improved and the refractive index can be increased, so that the amount of (meth) acrylate monomer units can be reduced, and the reduction in chemical resistance and the increase in manufacturing cost caused by the (meth) acrylate monomer units can be minimized. However, when the content of the first styrene monomer unit is lower than the above range, chemical resistance and gamma radiation resistance will be significantly reduced. On the other hand, when the content of the first styrene monomer unit is higher than the above range, transparency and impact resistance will be significantly reduced.

[0063] The graft copolymer may include 11.00 wt % to 46.00 wt %, preferably 15.00 wt % to 40.00 wt % of the (meth)acrylate monomer unit. When the above range is satisfied, the graft copolymer may achieve excellent transparency.

[0064] The graft copolymer may include 10.00 wt % to 36.00 wt %, preferably 15.00 wt % to 30.00 wt % of the second styrene-based monomer unit. When the above range is satisfied, the graft copolymer may achieve excellent processing properties.

[0065] The graft copolymer may further include an acrylonitrile monomer unit to further improve chemical resistance. The content of the acrylonitrile monomer unit may be 9.00 wt % or less, preferably 1.00 wt % to 9.00 wt %, to improve chemical resistance and minimize the occurrence of yellowing.

[0066] The weight average molecular weight of the graft copolymer may be 70,000 to 250,000 g / mol, preferably 100,000 to 200,000 g / mol. When the above range is satisfied, the chemical resistance and processability of the thermoplastic resin composition may be further improved.

[0067] In order to prepare the rubber polymer of the graft copolymer so that the rubber polymer has the above-mentioned conditions, an emulsion polymerization method is preferably used.

[0068] The non-graft copolymer may include a non-graft copolymer including a (meth)acrylate-based monomer unit and a second styrene-based monomer unit.

[0069] The non-graft copolymer may include 45.00 wt % to 70.00 wt %, preferably 50.00 wt % to 65.00 wt % of the (meth)acrylate monomer unit. When the above conditions are met, a thermoplastic resin composition having improved transparency may be prepared.

[0070] The non-graft copolymer may include 30.00 wt % to 55.00 wt %, preferably 35.00 wt % to 50.00 wt % of the second styrene-based monomer unit. When the above conditions are met, a thermoplastic resin composition having improved processability may be prepared.

[0071] The non-graft copolymer may further include an acrylonitrile monomer unit to further improve chemical resistance. The content of the acrylonitrile monomer unit may be 15.00 wt % or less, preferably 5.00 wt % to 15.00 wt %, to improve chemical resistance and minimize the occurrence of yellowing.

[0072] The weight average molecular weight of the non-graft copolymer may be 140,000 to 250,000 g / mol, preferably 160,000 to 230,000 g / mol. When the above range is satisfied, the chemical resistance and processability of the thermoplastic resin composition may be further improved.

[0073] Hereinafter, exemplary embodiments of the present invention will be described in detail so that those skilled in the art can easily implement the present invention. However, it should be understood that the present invention can be implemented in various forms, and these exemplary embodiments are not intended to limit the present invention thereto.

[0074] Preparation Example 1: Preparation of Graft Copolymer Powder A-1

[0075] A monomer mixture consisting of 30 wt % of styrene and 70 wt % of 1,3-butadiene was emulsion polymerized to prepare a styrene / butadiene rubber polymer latex having an average particle size of 350 nm and a refractive index of 1.5380.

[0076] 21.20 parts by weight of methyl methacrylate, 20.80 parts by weight of styrene, 3.00 parts by weight of acrylonitrile, 100 parts by weight of ion exchange water, 1.0 part by weight of sodium oleate, 0.05 parts by weight of tert-dodecyl mercaptan, 0.05 parts by weight of ethylenediaminetetraacetate, 0.1 parts by weight of sodium formaldehyde sulfoxylate, 0.001 parts by weight of ferrous sulfate and 0.2 parts by weight of cumene hydroperoxide are uniformly mixed to prepare a liquid mixture.

[0077] The reactor containing 55.00 parts by weight of styrene / butadiene rubber polymer latex was heated to 75° C., and the above liquid mixture was continuously added for 5 hours while polymerization was carried out. After the continuous addition was stopped, the reactor was heated to 80° C. and aged for 1 hour to terminate the polymerization reaction and obtain a graft copolymer latex.

[0078] The above graft copolymer latex was coagulated with calcium chloride, washed, dehydrated, and dried to obtain a graft copolymer powder A-1 having a refractive index of 1.5380 and a weight average molecular weight of 150,000 g / mol.

[0079] Preparation Example 2: Preparation of Graft Copolymer Powder A-2

[0080] A monomer mixture consisting of 10 wt % of styrene and 90 wt % of 1,3-butadiene was emulsion polymerized to prepare a styrene / butadiene rubber polymer latex having an average particle size of 300 nm and a refractive index of 1.5230.

[0081] 28.44 parts by weight of methyl methacrylate, 14.56 parts by weight of styrene, 7.00 parts by weight of acrylonitrile, 100 parts by weight of ion exchange water, 1.0 parts by weight of sodium oleate, 0.07 parts by weight of tert-dodecyl mercaptan, 0.05 parts by weight of ethylenediaminetetraacetate, 0.10 parts by weight of sodium formaldehyde sulfoxylate, 0.001 parts by weight of ferrous sulfate and 0.2 parts by weight of cumene hydroperoxide are uniformly mixed to prepare a liquid mixture.

[0082] The reactor containing 50.00 parts by weight of styrene / butadiene rubber polymer latex was heated to 75° C., and the above liquid mixture was continuously added for 5 hours while polymerization was carried out. After the continuous addition was stopped, the reactor was heated to 80° C. and aged for 1 hour to terminate the polymerization reaction and obtain a graft copolymer latex.

[0083] The above graft copolymer latex was coagulated with calcium chloride, washed, dehydrated, and dried to obtain a graft copolymer powder A-2 having a refractive index of 1.523 and a weight average molecular weight of 150,000 g / mol.

[0084] Preparation Example 3: Preparation of Graft Copolymer Powder A-3

[0085] A monomer mixture consisting of 15 wt % of styrene and 85 wt % of 1,3-butadiene was emulsion polymerized to prepare a styrene / butadiene rubber polymer latex having an average particle size of 300 nm and a refractive index of 1.5268.

[0086] 26.58 parts by weight of methyl methacrylate, 16.42 parts by weight of styrene, 7.00 parts by weight of acrylonitrile, 100 parts by weight of ion exchange water, 1.0 parts by weight of sodium oleate, 0.05 parts by weight of tert-dodecyl mercaptan, 0.05 parts by weight of ethylenediaminetetraacetate, 0.10 parts by weight of sodium formaldehyde sulfoxylate, 0.001 parts by weight of ferrous sulfate and 0.2 parts by weight of cumene hydroperoxide are uniformly mixed to prepare a liquid mixture.

[0087] The reactor containing 50.00 parts by weight of styrene / butadiene rubber polymer latex was heated to 75° C., and the above liquid mixture was continuously added for 5 hours while polymerization was carried out. After the continuous addition was stopped, the reactor was heated to 80° C. and aged for 1 hour to terminate the polymerization reaction and obtain a graft copolymer latex.

[0088] The above graft copolymer latex was coagulated with calcium chloride, washed, dehydrated, and dried to obtain a graft copolymer powder A-3 having a refractive index of 1.5268 and a weight average molecular weight of 170,000 g / mol.

[0089] Preparation Example 4: Preparation of Graft Copolymer Powder A-4

[0090] A monomer mixture consisting of 23 wt % of styrene and 77 wt % of 1,3-butadiene was emulsion polymerized to prepare a styrene / butadiene rubber polymer latex having an average particle size of 300 nm and a refractive index of 1.5330.

[0091] 24.90 parts by weight of methyl methacrylate, 20.10 parts by weight of styrene, 5.00 parts by weight of acrylonitrile, 100 parts by weight of ion exchange water, 1.0 part by weight of sodium oleate, 0.10 part by weight of tert-dodecyl mercaptan, 0.050 parts by weight of ethylenediaminetetraacetate, 0.100 parts by weight of sodium formaldehyde sulfoxylate, 0.001 parts by weight of ferrous sulfate and 0.2 parts by weight of cumene hydroperoxide are uniformly mixed to prepare a liquid mixture.

[0092] The reactor containing 50.00 parts by weight (based on solid content) of styrene / butadiene rubber polymer latex was heated to 75° C., and the above liquid mixture was continuously added for 5 hours while polymerization was carried out. After the continuous addition was stopped, the reactor was heated to 80° C. and aged for 1 hour to terminate the polymerization reaction and obtain a graft copolymer latex.

[0093] The above graft copolymer latex was coagulated with calcium chloride, washed, dehydrated, and dried to obtain a graft copolymer powder A-4 having a refractive index of 1.5330 and a weight average molecular weight of 130,000 g / mol.

[0094] Preparation Example 5: Preparation of Graft Copolymer Powder A-5

[0095] A monomer mixture consisting of 30 wt % of styrene and 70 wt % of 1,3-butadiene was emulsion polymerized to prepare a styrene / butadiene rubber polymer latex having an average particle size of 300 nm and a refractive index of 1.5379.

[0096] 21.00 parts by weight of methyl methacrylate, 22.00 parts by weight of styrene, 7.00 parts by weight of acrylonitrile, 100 parts by weight of ion exchange water, 1.0 part by weight of sodium oleate, 0.1 part by weight of tert-dodecyl mercaptan, 0.05 part by weight of ethylenediaminetetraacetate, 0.1 part by weight of sodium formaldehyde sulfoxylate, 0.001 part by weight of ferrous sulfate and 0.2 part by weight of cumene hydroperoxide are uniformly mixed to prepare a liquid mixture.

[0097] The reactor containing 50.00 parts by weight of styrene / butadiene rubber polymer latex was heated to 75° C., and the above liquid mixture was continuously added for 5 hours while polymerization was carried out. After the continuous addition was stopped, the reactor was heated to 80° C. and aged for 1 hour to terminate the polymerization reaction and obtain a graft copolymer latex.

[0098] The above graft copolymer latex was coagulated with calcium chloride, washed, dehydrated, and dried to obtain a graft copolymer powder A-5 having a refractive index of 1.5379 and a weight average molecular weight of 150,000 g / mol.

[0099] Preparation Example 6: Preparation of Graft Copolymer Powder A-6

[0100] A monomer mixture consisting of 35 wt % of styrene and 65 wt % of 1,3-butadiene was emulsion polymerized to prepare a styrene / butadiene rubber polymer latex having an average particle size of 300 nm and a refractive index of 1.5416.

[0101] 20.58 parts by weight of methyl methacrylate, 24.42 parts by weight of styrene, 5.00 parts by weight of acrylonitrile, 100 parts by weight of ion exchange water, 1.0 part by weight of sodium oleate, 0.03 parts by weight of tert-dodecyl mercaptan, 0.05 parts by weight of ethylenediaminetetraacetate, 0.1 parts by weight of sodium formaldehyde sulfoxylate, 0.001 parts by weight of ferrous sulfate and 0.2 parts by weight of cumene hydroperoxide are uniformly mixed to prepare a liquid mixture.

[0102] The reactor containing 50.00 parts by weight of styrene / butadiene rubber polymer latex was heated to 75° C., and the above liquid mixture was continuously added for 5 hours while polymerization was carried out. After the continuous addition was stopped, the reactor was heated to 80° C. and aged for 1 hour to terminate the polymerization reaction and obtain a graft copolymer latex.

[0103] The above graft copolymer latex was coagulated with calcium chloride, washed, dehydrated, and dried to obtain a graft copolymer powder A-6 having a refractive index of 1.5416 and a weight average molecular weight of 190,000 g / mol.

[0104] Preparation Example 7: Preparation of Graft Copolymer Powder A-7

[0105] A monomer mixture consisting of 6 wt % of styrene and 94 wt % of 1,3-butadiene was emulsion polymerized to prepare a styrene / butadiene rubber polymer latex having an average particle size of 300 nm and a refractive index of 1.5200.

[0106] 31.37 parts by weight of methyl methacrylate, 13.63 parts by weight of styrene, 5.00 parts by weight of acrylonitrile, 100 parts by weight of ion exchange water, 1.0 part by weight of sodium oleate, 0.10 parts by weight of tert-dodecyl mercaptan, 0.05 parts by weight of ethylenediaminetetraacetate, 0.1 parts by weight of sodium formaldehyde sulfoxylate, 0.001 parts by weight of ferrous sulfate and 0.2 parts by weight of cumene hydroperoxide are uniformly mixed to prepare a liquid mixture.

[0107] The reactor containing 50.00 parts by weight of styrene / butadiene rubber polymer latex was heated to 75° C., and the above liquid mixture was continuously added for 5 hours while polymerization was carried out. After the continuous addition was stopped, the reactor was heated to 80° C. and aged for 1 hour to terminate the polymerization reaction and obtain a graft copolymer latex.

[0108] The above graft copolymer latex was coagulated with calcium chloride, washed, dehydrated, and dried to obtain a graft copolymer powder A-7 having a refractive index of 1.52 and a weight average molecular weight of 130,000 g / mol.

[0109] Preparation Example 8: Preparation of Graft Copolymer Powder A-8

[0110] A monomer mixture consisting of 40 wt % of styrene and 60 wt % of 1,3-butadiene was emulsion polymerized to prepare a styrene / butadiene rubber polymer latex having an average particle size of 300 nm and a refractive index of 1.5454.

[0111] 18.72 parts by weight of methyl methacrylate, 26.28 parts by weight of styrene, 5.00 parts by weight of acrylonitrile, 100 parts by weight of ion exchange water, 1.0 parts by weight of sodium oleate, 0.10 parts by weight of tert-dodecyl mercaptan, 0.05 parts by weight of ethylenediaminetetraacetate, 0.1 parts by weight of sodium formaldehyde sulfoxylate, 0.001 parts by weight of ferrous sulfate and 0.2 parts by weight of cumene hydroperoxide are uniformly mixed to prepare a liquid mixture.

[0112] The reactor containing 50.00 parts by weight of styrene / butadiene rubber polymer latex was heated to 75° C., and the above liquid mixture was continuously added for 5 hours while polymerization was carried out. After the continuous addition was stopped, the reactor was heated to 80° C. and aged for 1 hour to terminate the polymerization reaction and obtain a graft copolymer latex.

[0113] The above graft copolymer latex was coagulated with calcium chloride, washed, dehydrated, and dried to obtain a graft copolymer powder A-8 having a refractive index of 1.5454 and a weight average molecular weight of 130,000 g / mol.

[0114] Preparation Example 9: Preparation of Graft Copolymer Powder A-9

[0115] 1,3-butadiene was emulsion polymerized to prepare a butadiene rubber polymer latex having an average particle size of 300 nm and a refractive index of 1.5160.

[0116] 24.90 parts by weight of methyl methacrylate, 20.10 parts by weight of styrene, 5.00 parts by weight of acrylonitrile, 100 parts by weight of ion exchange water, 1.0 part by weight of sodium oleate, 0.10 parts by weight of tert-dodecyl mercaptan, 0.05 parts by weight of ethylenediaminetetraacetate, 0.1 parts by weight of sodium formaldehyde sulfoxylate, 0.001 parts by weight of ferrous sulfate and 0.2 parts by weight of cumene hydroperoxide are uniformly mixed to prepare a liquid mixture.

[0117] The reactor containing 50.00 parts by weight of butadiene rubber polymer latex was heated to 75° C., and the above liquid mixture was continuously added for 5 hours while polymerization was carried out. After the continuous addition was stopped, the reactor was heated to 80° C. and aged for 1 hour to terminate the polymerization reaction and obtain a graft copolymer latex.

[0118] The graft copolymer latex was coagulated with calcium chloride, washed, dehydrated, and dried to obtain a graft copolymer powder A-9 having a refractive index of 1.5454 and a weight average molecular weight of 130,000 g / mol. The graft copolymer powder A-9 became opaque due to the difference in refractive index between the butadiene rubber polymer and the hard copolymer grafted onto the butadiene rubber polymer, so its refractive index was not measured.

[0119] Preparation Example 10: Preparation of Graft Copolymer Powder A-10

[0120] A monomer mixture consisting of 23 wt % of styrene and 77 wt % of 1,3-butadiene was emulsion polymerized to prepare a styrene / butadiene rubber polymer latex having an average particle size of 100 nm and a refractive index of 1.5330.

[0121] 24.90 parts by weight of methyl methacrylate, 20.10 parts by weight of styrene, 5.00 parts by weight of acrylonitrile, 100 parts by weight of ion exchange water, 1.0 part by weight of sodium oleate, 0.10 parts by weight of tert-dodecyl mercaptan, 0.05 parts by weight of ethylenediaminetetraacetate, 0.1 parts by weight of sodium formaldehyde sulfoxylate, 0.001 parts by weight of ferrous sulfate and 0.2 parts by weight of cumene hydroperoxide are uniformly mixed to prepare a liquid mixture.

[0122] The reactor containing 50.00 parts by weight of styrene / butadiene rubber polymer latex was heated to 75° C., and the above liquid mixture was continuously added for 5 hours while polymerization was carried out. After the continuous addition was stopped, the reactor was heated to 80° C. and aged for 1 hour to terminate the polymerization reaction and obtain a graft copolymer latex.

[0123] The above graft copolymer latex was coagulated with calcium chloride, washed, dehydrated, and dried to obtain a graft copolymer powder A-10 having a refractive index of 1.5330 and a weight average molecular weight of 100,000 g / mol.

[0124] Preparation Example 11: Preparation of Graft Copolymer Powder A-11

[0125] A monomer mixture consisting of 30 wt % of styrene and 70 wt % of 1,3-butadiene was emulsion polymerized to prepare a styrene / butadiene rubber polymer latex having an average particle size of 350 nm and a refractive index of 1.5380.

[0126] 21.20 parts by weight of methyl methacrylate, 20.80 parts by weight of styrene, 3.00 parts by weight of acrylonitrile, 100 parts by weight of ion exchange water, 1.0 part by weight of sodium oleate, 0.20 parts by weight of tert-dodecyl mercaptan, 0.3 parts by weight of ethylenediaminetetraacetate, 0.1 parts by weight of sodium formaldehyde sulfoxylate, 0.001 parts by weight of ferrous sulfate and 0.2 parts by weight of cumene hydroperoxide are uniformly mixed to prepare a liquid mixture.

[0127] The reactor containing 55.00 parts by weight of styrene / butadiene rubber polymer latex was heated to 75° C., and the above liquid mixture was continuously added for 5 hours while polymerization was carried out. After the continuous addition was stopped, the reactor was heated to 80° C. and aged for 1 hour to terminate the polymerization reaction and obtain a graft copolymer latex.

[0128] The above graft copolymer latex was coagulated with calcium chloride, washed, dehydrated, and dried to obtain a graft copolymer powder A-11 having a refractive index of 1.5380 and a weight average molecular weight of 80,000 g / mol.

[0129] Preparation Example 12: Preparation of Graft Copolymer Powder A-12

[0130] A monomer mixture consisting of 10 wt % of styrene and 90 wt % of 1,3-butadiene was emulsion polymerized to prepare a styrene / butadiene rubber polymer latex having an average particle size of 300 nm and a refractive index of 1.5230.

[0131] 33.00 parts by weight of methyl methacrylate, 16.00 parts by weight of styrene, 1.00 parts by weight of acrylonitrile, 100 parts by weight of ion exchange water, 1.0 parts by weight of sodium oleate, 0.15 parts by weight of tert-dodecyl mercaptan, 0.05 parts by weight of ethylenediaminetetraacetate, 0.1 parts by weight of sodium formaldehyde sulfoxylate, 0.001 parts by weight of ferrous sulfate and 0.2 parts by weight of cumene hydroperoxide are uniformly mixed to prepare a liquid mixture.

[0132] The reactor containing 50.00 parts by weight of styrene / butadiene rubber polymer latex was heated to 75° C., and the above liquid mixture was continuously added for 5 hours while polymerization was carried out. After the continuous addition was stopped, the reactor was heated to 80° C. and aged for 1 hour to terminate the polymerization reaction and obtain a graft copolymer latex.

[0133] The above graft copolymer latex was coagulated with calcium chloride, washed, dehydrated, and dried to obtain a graft copolymer powder A-12 having a refractive index of 1.5230 and a weight average molecular weight of 130,000 g / mol.

[0134] Preparation Example 13: Preparation of Graft Copolymer Powder A-13

[0135] 1,3-butadiene was emulsion polymerized to prepare a butadiene rubber polymer latex having an average particle size of 300 nm and a refractive index of 1.5160.

[0136] 35.00 parts by weight of methyl methacrylate, 12.00 parts by weight of styrene, 3.00 parts by weight of acrylonitrile, 100 parts by weight of ion exchange water, 1.0 part by weight of sodium oleate, 0.5 part by weight of tert-dodecyl mercaptan, 0.05 part by weight of ethylenediaminetetraacetate, 0.1 part by weight of sodium formaldehyde sulfoxylate, 0.001 part by weight of ferrous sulfate and 0.2 part by weight of cumene hydroperoxide are uniformly mixed to prepare a liquid mixture.

[0137] The reactor containing 50.00 parts by weight of butadiene rubber polymer latex was heated to 75° C., and the above liquid mixture was continuously added for 5 hours while polymerization was carried out. After the continuous addition was stopped, the reactor was heated to 80° C. and aged for 1 hour to terminate the polymerization reaction and obtain a graft copolymer latex.

[0138] The above graft copolymer latex was coagulated with calcium chloride, washed, dehydrated, and dried to obtain a graft copolymer powder A-13 having a refractive index of 1.5160 and a weight average molecular weight of 100,000 g / mol.

[0139] Preparation Example 14: Preparation of non-grafted copolymer particles B-1

[0140] A liquid mixture containing 44.10 parts by weight of methyl methacrylate, 44.90 parts by weight of styrene, 11.00 parts by weight of acrylonitrile, 30 parts by weight of toluene and 0.05 parts by weight of n-octyl mercaptan was continuously added to the reactor for an average polymerization time of 3 hours. In this case, the polymerization temperature was maintained at 148°C. The polymerization solution continuously discharged from the reactor was heated in a preheating tank, and unreacted monomers and solvents were volatilized in a volatilizer. Thereafter, the resulting polymer was extruded using a polymer transfer pump extruder while maintaining a temperature of 210°C, thereby preparing non-grafted copolymer particles B-1 having a refractive index of 1.5380 and a weight average molecular weight of 200,000 g / mol.

[0141] Preparation Example 15: Preparation of non-grafted copolymer particles B-2

[0142] A liquid mixture containing 60.52 parts by weight of methyl methacrylate, 30.48 parts by weight of styrene, 9.00 parts by weight of acrylonitrile, 30 parts by weight of toluene and 0.06 parts by weight of n-octyl mercaptan was continuously added to the reactor for an average polymerization time of 3 hours. In this case, the polymerization temperature was maintained at 148°C. The polymerization solution continuously discharged from the reactor was heated in a preheating tank, and unreacted monomers and solvents were volatilized in a volatilizer. Thereafter, the resulting polymer was extruded using a polymer transfer pump extruder while maintaining a temperature of 210°C, thereby preparing non-grafted copolymer particles B-2 having a refractive index of 1.5230 and a weight average molecular weight of 190,000 g / mol.

[0143] Preparation Example 16: Preparation of non-grafted copolymer particles B-3

[0144] A liquid mixture containing 56.72 parts by weight of methyl methacrylate, 34.28 parts by weight of styrene, 9.00 parts by weight of acrylonitrile, 30 parts by weight of toluene and 0.06 parts by weight of n-octyl mercaptan was continuously added to the reactor for an average polymerization time of 3 hours. In this case, the polymerization temperature was maintained at 148°C. The polymerization solution continuously discharged from the reactor was heated in a preheating tank, and unreacted monomers and solvents were volatilized in a volatilizer. Thereafter, the resulting polymer was extruded using a polymer transfer pump extruder while maintaining a temperature of 210°C, thereby preparing non-grafted copolymer particles B-3 having a refractive index of 1.5268 and a weight average molecular weight of 190,000 g / mol.

[0145] Preparation Example 17: Preparation of non-grafted copolymer particles B-4

[0146] A liquid mixture containing 52.00 parts by weight of methyl methacrylate, 39.00 parts by weight of styrene, 9.00 parts by weight of acrylonitrile, 30 parts by weight of toluene and 0.06 parts by weight of n-octyl mercaptan was continuously added to the reactor for an average polymerization time of 3 hours. In this case, the polymerization temperature was maintained at 148°C. The polymerization solution continuously discharged from the reactor was heated in a preheating tank, and unreacted monomers and solvents were volatilized in a volatilizer. Thereafter, the resulting polymer was extruded using a polymer transfer pump extruder while maintaining a temperature of 210°C, thereby preparing non-grafted copolymer particles B-4 having a refractive index of 1.5315 and a weight average molecular weight of 190,000 g / mol.

[0147] Preparation Example 18: Preparation of non-grafted copolymer particles B-5

[0148] A liquid mixture containing 45.62 parts by weight of methyl methacrylate, 45.38 parts by weight of styrene, 9.00 parts by weight of acrylonitrile, 30 parts by weight of toluene and 0.06 parts by weight of n-octyl mercaptan was continuously added to the reactor for an average polymerization time of 3 hours. In this case, the polymerization temperature was maintained at 148°C. The polymerization solution continuously discharged from the reactor was heated in a preheating tank, and unreacted monomers and solvents were volatilized in a volatilizer. Thereafter, the resulting polymer was extruded using a polymer transfer pump extruder while maintaining a temperature of 210°C, thereby preparing non-grafted copolymer particles B-5 having a refractive index of 1.5379 and a weight average molecular weight of 190,000 g / mol.

[0149] Preparation Example 19: Preparation of non-grafted copolymer particles B-6

[0150] A liquid mixture containing 41.92 parts by weight of methyl methacrylate, 49.08 parts by weight of styrene, 9.00 parts by weight of acrylonitrile, 30 parts by weight of toluene and 0.06 parts by weight of n-octyl mercaptan was continuously added to the reactor for an average polymerization time of 3 hours. In this case, the polymerization temperature was maintained at 148°C. The polymerization solution continuously discharged from the reactor was heated in a preheating tank, and unreacted monomers and solvents were volatilized in a volatilizer. Thereafter, the resulting polymer was extruded using a polymer transfer pump extruder while maintaining a temperature of 210°C, thereby preparing non-grafted copolymer particles B-6 having a refractive index of 1.5416 and a weight average molecular weight of 190,000 g / mol.

[0151] Preparation Example 20: Preparation of non-grafted copolymer particles B-7

[0152] A liquid mixture containing 63.52 parts by weight of methyl methacrylate, 27.48 parts by weight of styrene, 9.00 parts by weight of acrylonitrile, 30 parts by weight of toluene and 0.06 parts by weight of n-octyl mercaptan was continuously added to the reactor for an average polymerization time of 3 hours. In this case, the polymerization temperature was maintained at 148°C. The polymerization solution continuously discharged from the reactor was heated in a preheating tank, and unreacted monomers and solvents were volatilized in a volatilizer. Thereafter, the resulting polymer was extruded using a polymer transfer pump extruder while maintaining a temperature of 210°C, thereby preparing non-grafted copolymer particles B-7 having a refractive index of 1.5200 and a weight average molecular weight of 190,000 g / mol.

[0153] Preparation Example 21: Preparation of non-grafted copolymer particles B-8

[0154] A liquid mixture containing 38.12 parts by weight of methyl methacrylate, 52.88 parts by weight of styrene, 9.00 parts by weight of acrylonitrile, 30 parts by weight of toluene and 0.06 parts by weight of n-octyl mercaptan was continuously added to the reactor for an average polymerization time of 3 hours. In this case, the polymerization temperature was maintained at 148°C. The polymerization solution continuously discharged from the reactor was heated in a preheating tank, and unreacted monomers and solvents were volatilized in a volatilizer. Thereafter, the resulting polymer was extruded using a polymer transfer pump extruder while maintaining a temperature of 210°C, thereby preparing non-grafted copolymer particles B-8 having a refractive index of 1.5454 and a weight average molecular weight of 190,000 g / mol.

[0155] Preparation Example 22: Preparation of non-grafted copolymer particles B-9

[0156] A liquid mixture containing 56.72 parts by weight of methyl methacrylate, 34.28 parts by weight of styrene, 9.00 parts by weight of acrylonitrile, 30 parts by weight of toluene and 0.01 parts by weight of n-octyl mercaptan was continuously added to the reactor for an average polymerization time of 3 hours. In this case, the polymerization temperature was maintained at 148°C. The polymerization solution continuously discharged from the reactor was heated in a preheating tank, and unreacted monomers and solvents were volatilized in a volatilizer. Thereafter, the resulting polymer was extruded using a polymer transfer pump extruder while maintaining a temperature of 210°C, thereby preparing non-grafted copolymer particles B-9 having a refractive index of 1.5268 and a weight average molecular weight of 350,000 g / mol.

[0157] Preparation Example 23: Preparation of non-grafted copolymer particles B-10

[0158] A liquid mixture containing 44.10 parts by weight of methyl methacrylate, 44.90 parts by weight of styrene, 11.00 parts by weight of acrylonitrile, 30 parts by weight of toluene and 0.3 parts by weight of n-octyl mercaptan was continuously added to the reactor for an average polymerization time of 3 hours. In this case, the polymerization temperature was maintained at 148°C. The polymerization solution continuously discharged from the reactor was heated in a preheating tank, and unreacted monomers and solvents were volatilized in a volatilizer. Thereafter, the resulting polymer was extruded using a polymer transfer pump extruder while maintaining a temperature of 210°C, thereby preparing non-grafted copolymer particles B-10 having a refractive index of 1.5380 and a weight average molecular weight of 90,000 g / mol.

[0159] Preparation Example 24: Preparation of non-grafted copolymer particles B-11

[0160] A liquid mixture containing 63.50 parts by weight of methyl methacrylate, 31.50 parts by weight of styrene, 5.00 parts by weight of acrylonitrile, 30 parts by weight of toluene and 0.08 parts by weight of n-octyl mercaptan was continuously added to the reactor for an average polymerization time of 3 hours. In this case, the polymerization temperature was maintained at 148°C. The polymerization solution continuously discharged from the reactor was heated in a preheating tank, and unreacted monomers and solvents were volatilized in a volatilizer. Thereafter, the resulting polymer was extruded using a polymer transfer pump extruder while maintaining a temperature of 210°C, thereby preparing non-grafted copolymer particles B-11 having a refractive index of 1.5230 and a weight average molecular weight of 190,000 g / mol.

[0161] Preparation Example 25: Preparation of non-grafted copolymer particles B-12

[0162] A liquid mixture containing 70.40 parts by weight of methyl methacrylate, 24.60 parts by weight of styrene, 5.00 parts by weight of acrylonitrile, 30 parts by weight of toluene and 0.1 parts by weight of n-octyl mercaptan was continuously added to the reactor for an average polymerization time of 3 hours. In this case, the polymerization temperature was maintained at 148°C. The polymerization solution continuously discharged from the reactor was heated in a preheating tank, and unreacted monomers and solvents were volatilized in a volatilizer. Thereafter, the resulting polymer was extruded using a polymer transfer pump extruder while maintaining a temperature of 210°C, thereby preparing non-grafted copolymer particles B-12 having a refractive index of 1.5160 and a weight average molecular weight of 150,000 g / mol.

[0163] Examples and Comparative Examples

[0164] The graft copolymer powder and the non-graft copolymer particles were uniformly mixed in the contents shown in Tables 1 to 3 to prepare a thermoplastic resin composition.

[0165] Test Example 1

[0166] Physical properties of the thermoplastic resin compositions according to Examples and Comparative Examples were measured by the methods described below, and the results thereof are shown in Tables 1 to 3.

[0167] 1) Weight average molecular weight (g / mol): 1 g of the thermoplastic resin composition was dissolved in 50 g of acetone while stirring for 24 hours, and then centrifuged in a centrifuge (SUPRA30K manufactured by Hanil Science Industrial) at 16,000 rpm and -10°C for 4 hours to separate a supernatant and a precipitate, and the supernatant was dried in a hot air dryer set at 50°C for 12 hours to obtain a dry solid. The obtained dry solid was dissolved in tetrahydrofuran at a concentration of 1% by weight and then filtered through a 1 μm filter, and then the weight average molecular weight was measured by gel permeation chromatography (GPC) as a relative value relative to a standard polystyrene sample.

[0168] Meanwhile, in the GPC measurement, Agilent 1200 series system was used, and the measurement conditions were as follows.

[0169] Refractive index detector (RI): Agilent G1362 RID

[0170] RI temperature: 35℃

[0171] Data processing: Agilent ChemStation S / W

[0172] Solvent: Tetrahydrofuran

[0173] Column temperature: 40°C

[0174] Flow rate: 0.3ml / min

[0175] Sample concentration: 2.0mg / ml

[0176] Injection volume: 10μm

[0177] Column model: 1×PLgel 10μm MiniMix-B (250×4.6mm) + 1×PLgel 10μm MiniMix-B (250×4.6mm) + 1×PLgel 10μm MiniMix-B Guard (50×4.6mm)

[0178] Standard sample: polystyrene

[0179] 2) Methyl methacrylate unit / second styrene unit (MMA unit / ST unit): by using Nicolet TM iS20 FTIR spectrometer (manufactured by Thermo Scientific) obtains the weight of styrene units not included in the rubber polymer and the weight of methyl methacrylate units in the thermoplastic resin composition by infrared (IR) spectroscopy, and then calculates the weight ratio of methyl methacrylate units to styrene units.

[0180] Test Example 2

[0181] 100 parts by weight of each thermoplastic resin composition according to the examples and comparative examples, 0.3 parts by weight of a lubricant and 0.2 parts by weight of an antioxidant were uniformly mixed, and the resulting mixture was extruded using a twin-screw extrusion kneader (whose barrel temperature was 220° C.) to prepare pellets. The physical properties of the pellets were measured by the following methods, and the results are shown in Tables 1 to 3.

[0182] 1) Melt flow index (g / 10 min): measured according to ASTM D1238 at 220°C and 10 kg.

[0183] Test Example 3

[0184] The pellets prepared in Test Example 2 were injection molded to prepare test specimens. Physical properties of the test specimens were measured by the following methods, and the results are shown in Tables 1 to 3 below.

[0185] 1) Haze value (%): The transparency of a test specimen (thickness: 1 / 8 inch) was measured in accordance with ASTM D1003.

[0186] 2) Notched IZOD impact strength (kgf·cm / cm, 1 / 4 inch): measured at 23°C according to ASTM D256.

[0187] 3) Chemical resistance: The sample fixed on the 0.5% strain fixture was coated with 70% isopropyl alcohol and then observed for 10 minutes. No change was indicated as OK, and cracks were indicated as NG.

[0188] 4) Gamma radiation discoloration: L, a and b values ​​of 3 mm thick specimens were measured according to ASTM D2244. In addition, L, a and b values ​​were measured according to ASTM D2244 after 3 mm thick specimens were irradiated with gamma rays and stored for 21 days.

[0189]

[0190] In the above formula, L1, a1 and b1 are the L, a and b values ​​measured in the CIE LAB color coordinate system of the sample irradiated with gamma rays after storage for 21 days, and L2, a2 ​​and b2 are the L, a and b values ​​measured in the CIE LAB color coordinate system of the sample not irradiated with gamma rays.

[0191] [Table 1]

[0192]

[0193] [Table 2]

[0194]

[0195] [Table 3]

[0196]

[0197] Referring to Tables 1 to 3, for Examples 1 to 6, which use styrene / butadiene rubber polymers prepared by polymerizing 10 wt% to 35 wt% styrene and 65 wt% to 90 wt% 1,3-butadiene, the processability, transparency, impact resistance, chemical resistance, and gamma radiation resistance are excellent. However, for Comparative Example 1, which uses styrene / butadiene rubber polymers prepared by polymerizing 6 wt% styrene and 94 wt% 1,3-butadiene, the chemical resistance and gamma radiation resistance are significantly reduced compared to Examples 1 to 6.

[0198] For Comparative Example 2, a styrene / butadiene rubber polymer prepared by polymerizing 40 wt % of styrene and 60 wt % of 1,3-butadiene was used, and the transparency and impact resistance were significantly reduced compared to Examples 1 to 6.

[0199] Meanwhile, for Comparative Example 3, in which the weight average molecular weight of the thermoplastic resin composition was 270,000 g / mol, molding could not be performed during injection molding due to the excessively high weight average molecular weight. Therefore, its physical properties could not be evaluated.

[0200] For Comparative Example 4, which used a butadiene rubber polymer having an average particle size of 300 nm, the transparency was significantly reduced.

[0201] For Comparative Example 5, which used a styrene / butadiene rubber polymer having an average particle size of 100 nm, the impact resistance was significantly reduced.

[0202] For Comparative Examples 6 and 7, in which the weight average molecular weight of the thermoplastic resin composition was 85,000 g / mol, the chemical resistance was significantly decreased.

[0203] For Comparative Example 8, in which the weight ratio of the (meth)acrylate-based monomer unit to the second styrene-based monomer unit was about 2.04, transparency, chemical resistance, and gamma radiation resistance were significantly reduced.

[0204] For Comparative Example 9, in which the weight ratio of the (meth)acrylate-based monomer unit to the second styrene-based monomer unit was about 2.88, chemical resistance was reduced due to excessive inclusion of methyl methacrylate units, and manufacturing costs were increased due to excessive use of expensive raw material methyl methacrylate.

Claims

1. A thermoplastic resin composition comprising: A graft copolymer, the graft copolymer comprising: a rubber polymer, the rubber polymer comprising a first styrene monomer unit and a diene monomer unit in a weight ratio of 10:90 to 35:65, and an average particle size of 250 to 450 nm, (meth)acrylate monomer units grafted onto the rubber polymer, a second styrenic monomer unit grafted onto the rubber polymer, acrylonitrile monomer units grafted onto the rubber polymer; and A non-grafted copolymer, the non-grafted copolymer comprising a (meth)acrylate monomer unit, a second styrene monomer unit and an acrylonitrile monomer unit; in, The weight ratio of the (meth)acrylic acid ester monomer unit to the second styrene monomer unit is 2 or less, and The weight average molecular weight of the thermoplastic resin composition is 130,000 to 250,000 g / mol, which is measured as a relative value relative to a standard polystyrene sample by gel permeation chromatography after the thermoplastic resin composition is dissolved in acetone and then centrifuged to separate a supernatant and a precipitate, and the supernatant is dried, dissolved in tetrahydrofuran and filtered, Wherein, the thermoplastic resin composition comprises 20.00 wt % to 40.00 wt % of the rubber polymer; 23.00 wt % to 51.00 wt % of the (meth)acrylate monomer unit; 18.00 wt % to 41.00 wt % of the second styrene monomer unit; and 3.00 wt % to 12.00 wt % of the acrylonitrile monomer unit.

2. The thermoplastic resin composition according to claim 1, wherein A weight ratio of the (meth)acrylic acid ester-based monomer unit to the second styrene-based monomer unit is in the range of 0.80 to 2.

00.

3. The thermoplastic resin composition according to claim 1, wherein The thermoplastic resin composition has a weight average molecular weight of 140,000 to 210,000 g / mol.

4. The thermoplastic resin composition according to claim 1, wherein The refractive index of the graft copolymer is 1.5230 to 1.5420.

5. The thermoplastic resin composition according to claim 1, wherein The graft copolymer has a weight average molecular weight of 70,000 to 250,000 g / mol.

6. The thermoplastic resin composition according to claim 1, wherein The non-grafted copolymer has a weight average molecular weight of 140,000 to 250,000 g / mol.

Citation Information

Patent Citations

  • Wearable devices that include multiple biometrics

    KR1020200060730A

  • Latex composition for dip-forming, article formed by the composition and method for preparing the article formed

    KR1020210041215A

  • Process for producing enlarged latex

    CN1409727A

  • Thermoplastic resin composition and molded article

    JP2008260786A